Budi Mkitchen for flood victims - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; Ismail, Amelia Ritahani; et al. (mKitchen, 2021)
This book narrates mKitchen in assisting flood victims. The first part of the book reflects the history and development of mKitchen. mKitchen sticks to its vision, mission and objectives. In any event, mKitchen must not deviate from its founding objectives. The second part of the book narrates the humanitarian mission of mKitchen through food distribution for flood victims at selected places. Finally, the book records appreciation to mKitchen junior from IIUM for being the first batch as torch bearers of mKitchen on wider scale or rahmatan lil ‘alamin.